The Influence of Employee Engagement and Job Security on Job Satisfaction among Employees of the Protocol and Leadership Communication Section of Surabaya City Government - Jefry; Nuri Herachwat (Majapahit Journal of Islamic Finance and Management, 2026)
This study investigates the influence of employee engagement and job security on job satisfaction among employees of the Protocol and Leadership Communication Section of the Surabaya City Government. Employee engagement is conceptualized as the emotional and cognitive connection that employees have with their work, while job security refers to employees’ perception of stability and continuity in their employment. A quantitative explanatory research design was employed, utilizing a saturated sampling technique due to the limited population size of fewer than 30 employees. Data were collected through a structured questionnaire using a five-point Likert scale. The instrument consisted of eight items for employee engagement, eight items for job security, and eight items for job satisfaction. Validity and reliability tests were conducted using SPSS 26, followed by multiple linear regression analysis to examine both partial and simultaneous effects. The findings are expected to provide empirical evidence on how engagement and perceived security contribute to overall job satisfaction within government institutions, particularly in high-demand communication and protocol functions.